Development and assessment of a model predictive controller enabling anticipatory control strategies for a heat-pipe system. (February 2023) - Lin, Linyu; Oncken, Joseph; Agarwal, Vivek; Permann, Cody; Gribok, Andrei; McJunkin, Timothy; Eggers, Shannon; Boring, Ronald
Abstract: To support the reliable and resilient operation of modular reactors and microreactors, anticipatory control strategies have been proposed for achieving faster-than-real-time predictions and decision-making capabilities in anticipation of potential anomalies, including setpoint changes and cyber incidents. This work presents how anticipatory control strategies can be implemented via model predictive control (MPC) for a single heat pipe's temperature. Considering the uncertainty in developing and applying MPC, this work evaluates MPC performance given three different model forms: a linear response surface model, an artificial neural network (ANN), and an autoregressive model with exogenous input (ARX). This work also evaluates the impacts of different input biases and variance on MPC performance in order to account for potential sensor reading variations due to cyber incidents. We observe that the ANN and ARX result in more fluctuated control actions compared to the MPC with linear response surface model. However, when the cyber incidents are of large magnitudes, the linear response surface model produces smaller feasible regions than the ANN and ARX models under identical constraints.